2019
DOI: 10.15575/biodjati.v4i1.4389
|View full text |Cite
|
Sign up to set email alerts
|

Non-Destructive Classification of Fruits Based on Vis-nir Spectroscopy and Principal Component Analysis

Abstract: Fruits are one of the sources of nutrition needed for health. Fruit quality is generally assessed by physical and chemical properties. Measurement of fruit internal quality is usually done by destructive techniques. Ultraviolet, visible and near-infrared (UV-Vis-NIR) spec-troscopy is a non-destructive technique to measure fruit quality. This technique can rapidly measure the fruit quality, the measured fruit still remains intact, and can be marketed. Besides, UV-Vis-NIR spectrosco-py can also be used to classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 10 publications
0
1
0
2
Order By: Relevance
“…Naik and Patel reviewed the literature on fruit classification and grading [27]. They explored the classification and grading capabilities of popular machine learning methods such as artificial neural networks [28], biogeography-based optimization [29], support vector machines [30], and principal component analysis [31] under different fruits. Their results confirmed that machine learning could achieve fruit detection, tracking, and estimation.…”
Section: Resultsmentioning
confidence: 99%
“…Naik and Patel reviewed the literature on fruit classification and grading [27]. They explored the classification and grading capabilities of popular machine learning methods such as artificial neural networks [28], biogeography-based optimization [29], support vector machines [30], and principal component analysis [31] under different fruits. Their results confirmed that machine learning could achieve fruit detection, tracking, and estimation.…”
Section: Resultsmentioning
confidence: 99%
“…PCA berfokus pada berbagai variasi dari spektrum dan mengubahnya menjadi varibel-variabel baru yang tidak saling berkorelasi. PCA telah banyak digunakan untuk mengelompokkan berbagai produk pertanian [7]- [11]. Metode PCA dapat diaplikasikan salah satu tujuannya yaitu untuk grading komoditas hortikultura.…”
Section: Pendahuluanunclassified
“…Hal ini menjelaskan bahwa sebanyak 90% data keragaman dapat dijabarkan di PC1 dan 7% data keragaman dapat dijelaskan di PC2. Sejalan dengan penelitian lainnya yang menyebutkan bahwa dengan metode PCA dan spectroscopy didapatkan keakuratan 100% pada berbagai produk khususnya dalam bidang pertanian [7], [9], [16].…”
Section: Diskriminasi Menggunakan Metode Pca Pada Buah Cabai Rawit Domba Berbagai Tingkat Kematanganunclassified